-7(8 + k)
-56 + 7k
-7k - 56
-7k + 56

Question

Asked 3/5/2013 9:13:25 AM

Updated 7/9/2014 10:41:00 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

lechatelier|Points 86|

sunny4691|Points 983|

Solution: 8y(y - 4) + 3y(y + 2) = 8y^2 - 32y + 3y^2 + 6y = 11y^2 - 26y

Shey091808|Points 863|

AttyK|Points 145|

Question

Asked 3/5/2013 9:13:25 AM

Updated 7/9/2014 10:41:00 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

There are no new answers.

Solve for x.
5x - 6 = 4x + 8
**Weegy:** x=-0.91 is the answer. **User:** If $400 is invested at the rate of 6% for one year, what will be the total value of the investment (the amount)?
**Weegy:** First calculate the simple interes. I=prt = 400*.06*1 = 24. Then add the interest to the principle. 400+24=424. The total value of the investment will be $424. (More)

Question

Expert Answered

Asked 3/4/2013 12:11:43 PM

0 Answers/Comments

15% of $75
**Weegy:** Hello, How are you , can I answer a question for you ? **User:** WHAT IS 15% OF $75! **Weegy:** Hello, How are you , can I answer a question for you ? (More)

Question

Updated 11/27/2014 5:32:37 AM

1 Answer/Comment

15% of 75 is 11.25

.15 x 75 = 11.25

.15 x 75 = 11.25

Added 11/27/2014 5:32:36 AM

This answer has been confirmed as correct and helpful.

Simplify the given equation.
17x - 6 + 3x - 5 = x + 11 + 4x
20x - 11 = 5x + 11
20x + 1 = 5x + 11
9x = 16x **Weegy:** 20x-11=5x+11 **User:** Solve for x.
7x + 9 = 6x - 5
**Weegy:** 5x - 6 = 4x + 8, 5x - 4x = 8 + 6, x = 14 **User:** Solve for x.
5x - 6 = 4x + 8
(More)

Question

Updated 5/28/2014 10:52:30 PM

2 Answers/Comments

7x + 9 = 6x - 5

7x - 6x = -5 - 9

x = -14

7x - 6x = -5 - 9

x = -14

Added 5/28/2014 10:52:08 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/28/2014 10:54:54 PM]

5x - 6 = 4x + 8

5x - 4x = 8 + 6

x = 14

5x - 4x = 8 + 6

x = 14

Added 5/28/2014 10:52:30 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/28/2014 10:55:31 PM]

x 3(x 2 + 5x + 1)
x6+ 5x4+x3
x5+ 5x4+x3
x5+ 5x3+x3 **Weegy:** The answer is (b) x5+ 5x4+x3 **User:** Find the product.
-y(2y 3 - 8)
-y4+ 4y
y4+ 4y
-2y3+ 4
**Weegy:** a **User:** Select the correct product.
(x2 + 4x + 8)(2x - 1)
2x3+ 7x2+ 12x- 8
2x3- 7x2- 12x- 8
x2+ 6x+ 7
x2+ 8x- 8 **Weegy:** The correct answer to the presented problem is (a) 2x3 + 7x2 + 12x - 8 **User:** Select the correct product.
(6 - d)(d2 - 5 + 3d)
6d2- 30d
d3- 3d2- 23d+ 30
d2+ 2d- 30
-d3+ 3d2+ 23d- 30 **Weegy:** 6d2- 30d d3- 3d **User:** (y + z)3
y3+z3
y3+ 3y2z+ 3yz2+z3
3y+ 3z
y3z3 (More)

Question

Updated 6/26/2014 12:50:10 AM

2 Answers/Comments

Simplify (8z - 10) ÷ (-2) + 5(z - 1).
z
z - 1
z - 2
**Weegy:** 2(4z-5)/-7+5z This is the simplified form. (More)

Question

Updated 3/6/2013 6:11:32 AM

1 Answer/Comment

(8z - 10) ÷ (-2) + 5(z - 1)

= 5 - 4z + 5z - 5

= z

= 5 - 4z + 5z - 5

= z

Added 3/6/2013 6:11:32 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [6/21/2014 1:58:11 PM], Rated good by andrewpallarca

39,061,558

questions answered

There are no comments.